Letter (copy) : Child Refugees - Tewson, Vincent
1939-02-20 038-0102-001 Secretary's. HVT/FP/261 20th February, 1939. Mr. R. Vallance, 10, Bradder Street, Mansfield, Notts. Dear Sir, Child Refugees. Thank you very much for your letter received this morning, asking for information regarding the adoption of refugee children. I would suggest that you communicate either with the Secretary of the Basque Children's Committee, 4, Great Smith Street, London, S.W.1., or with the World Movement for Care of Children Coming from Germany, Bloomsbury House, Bloomsbury Street, London, W.C.1. Yours sincerely, Assistant Secretary. 292/946/38/102(I)